Analisis Perbandingan Efektivitas Penggunaan Material Kevlar dan Serat Boron pada Pesawat UAV MALE Berbasis Inovasi Winglet - Ringgit Purbowati; Sovian Aritonang (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study was conducted to examine the effectiveness of Kevlar as a structural material in Medium Altitude Long Endurance (MALE) Unmanned Aerial Vehicles (UAVs), particularly those designed with winglet innovations. In UAV development, material selection plays a crucial role since it directly affects flight performance, fuel efficiency, and the overall durability of the aircraft structure. Kevlar is widely recognized as a lightweight yet highly durable material, making it an interesting candidate to replace more conventional options such as aluminum and carbon fiber composites. Two approaches were applied in this research: numerical simulations using aerodynamic software and experimental testing on a prototype wing and winglet reinforced with Kevlar. The analysis focused on comparing lift, drag, total aircraft weight, and fuel consumption between Kevlar-based structures and conventional materials. The results demonstrate that Kevlar significantly improves aerodynamic efficiency and extends flight endurance due to its lower weight. Moreover, Kevlar exhibits superior resistance to dynamic loads and impacts, which are critical during certain flight conditions. However, challenges remain in terms of higher production costs and more complex manufacturing processes compared to traditional materials. Despite these limitations, the findings provide valuable insights for developing more efficient and durable MALE UAVs, while also encouraging innovation in aerodynamic design through the application of winglet technology.